Cursed financial innovation - Péter Kondor; Botond Köszegi (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
We analyze the welfare properties of derivative securities that profit-maximizing issuers offer to investors who have inferior information and neglect the information content of the offer. To capture the markets for structured securities and exotic exchange-traded funds, we assume that issuers can choose both the underlying asset and the form of the security. An issuer's optimal security induces investors to bet on unlikely market movements, creating both excess risk taking and undersaving. Giving more information to the issuer leads it to choose an underlying asset on which its information is more extreme, exacerbating both effects and hence lowering social welfare. Furthermore, providing inferior and noisy additional information to investors also lowers welfare because the security is then written on an underlying asset about which the information is misleading. If the issuer can base its security on a combination of underlying assets, it optimally creates a "custom-designed" index to maximize its informational advantage and minimize risk, minimizing investor and social welfare. Restricting the set of underlying assets - a kind of standardization - increases welfare by preventing the issuer from systematically selling a security with extreme or misleading information. Once this policy is adopted, increasing investor information becomes beneficial.
Keywords: 330